Dual-band high-gain shared-aperture antenna integrating fabry-perot and reflectarray mechanisms - Yi, Xianjin (2023)
This work presents a dual-band high-gain shared-aperture antenna. The proposed antenna integrates both the Fabry-Perot and reflectarray mechanisms; the antenna works as a Fabry-Perot cavity antenna (FPCA) in the S-band (2.45 GHz) and as a reflectarray antenna (RA) in the Xband (10 GHz). The antenna has a simple structure made up of only two printed circuit board layers. The bottom layer acts as a source antenna, a ground plane for the FPCA, and as a reflective surface for the RA. The upper layer contains the source antenna for the RA and serves as a partially reflective superstrate for the FPCA. The FPCA and RA thus share the same physical aperture but function independently. As an example, we design, fabricate, and characterize an antenna that operates at 2.45 and 10 GHz with an aperture size of 300 × 300 mm2. The measured results are found to be in good agreement with the simulations. We show that the proposed antenna achieves a gain of 16.21 dBi at 2.45 GHz and 21.6 dBi at 10 GHz with a −10 dB impedance bandwidths of 2.39–2.66 GHz and 9.40–10.28 GHz. The isolation between the two antenna ports is found to be larger than 30 dB.